Global Challenges – an innovative journal for tackling humanity's major challenges. Issue 1 (21st September 2015) - Hutton, Fiona G.; Feulner, Georg; Lund, Peter D.; Henson, Spencer; Røttingen, John‐Arne; Hoffman, Steven J.; Butler, David
Abstract :